2022
DOI: 10.3389/fpsyg.2022.1042705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different sport environments on proactive and reactive motor inhibition: A study on open- and closed-skilled athletes via mouse-tracking procedure

Abstract: This study aimed to investigate the effect of different sport environments (open-and closed-skill sports) on proactive and reactive inhibitory processes as two distinct components of motor inhibition. A mouse-tracking procedure was employed to compare behavioral performance among three groups of participants (tennis players, swimmers and non-athletes) in non-sport-specific cued Go/No-Go (GNG) and Stop Signal Task (SST), which mainly engage proactive and reactive inhibitory control, respectively. Reaction times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…This task was initially validated by the seminal studies of Donders (see [67]) and has been extensively replicated over time. We applied a version similar to other works published by our group [65,68,69]. Briefly, the visual targets were white arrows presented on a gray background at the center of a touch-screen monitor.…”
Section: Taskmentioning
confidence: 99%
“…This task was initially validated by the seminal studies of Donders (see [67]) and has been extensively replicated over time. We applied a version similar to other works published by our group [65,68,69]. Briefly, the visual targets were white arrows presented on a gray background at the center of a touch-screen monitor.…”
Section: Taskmentioning
confidence: 99%
“…In the broad range of definitions related to higher cognition, executive functions are identified as a group of capacities crucial for conscious and directed behavior control toward achieving specific goals (Diamond, 2013). These functions are essential for overcoming cognitive challenges in sports environments by facilitating the coordination between thought and action to achieve adaptive goals (Bravi et al, 2022). The study of the interaction between sports practice and cognitive functions promises not only to identify and enhance athletic talent (Scharfen and Memmert, 2019), but also to evaluate specific sports as potential interventions to enhance cognitive abilities in individuals with cognitive impairments, benefiting both young people and older adults (Tsai, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Especially in elite sports, being able to inhibit a movement at a late time seems beneficial, because of very dynamic and fast-changing playing situations as well as time-critical movements. In this vein, some studies have examined whether elite athletes perform better on cognitive tasks (Mann et al, 2007 ; Voss et al, 2010 ; Heppe et al, 2016 ) and in a response-inhibition task compared to non-athletes (Zhang et al, 2015 ; Brevers et al, 2018 ; Bravi et al, 2022 ) and recreational athletes. Most studies showed that elite athletes perform better in a response inhibition task than recreational athletes.…”
Section: Introductionmentioning
confidence: 99%